Clinical and Histopathological Features of Ovarian Cancer in Iraq, Baghdad Between 2014-2020 - Mohamad, Ban Jasim; Zghair, Faiza Aftan (Iraqi Journal of Science, 2022)
Ovarian cancer is a heterogeneous disease with disparities in clinical performance and consequences. It is a cluster of numerous subtypes with diverse biological topographies that cause alterations in response to treatments, relapse rates, and endurance. This task was designed to investigate the epidemiology of the diagnosed cases of ovarian cancer from 2014 to 2020 in Baghdad. A total of 51 cases of different ovarian cancer samples were collected from Al-Elwea Maternity Hospital and Medical City Teaching Hospital, Baghdad. Clinical information including patients' age, tumor size and location, pathological grade and stage were also collected. Results revealed high incidence of OC in patients at age of ˂55 years for the rate 59%. The most common type was epithelial serous ovarian cancer by 52.9% overall, with high frequency at right ovary by 63.3%.  The dominant tumor size was 5cm in malignant cases. While the most frequent tumor stage was stage IC with rate of 29.6%, and Grade 3 was the foremost one by 40.7%. Conclusion: The most common type of cancer is epithelial serous ovarian cancer that occur in patients younger than 55years and presented at early stage of disease (IC) with high tumor grade (poor differentiation) at the time of diagnosis